2017
DOI: 10.3390/en10121998
|View full text |Cite
|
Sign up to set email alerts
|

A New Prediction Model for Transformer Winding Hotspot Temperature Fluctuation Based on Fuzzy Information Granulation and an Optimized Wavelet Neural Network

Abstract: Abstract:Winding hotspot temperature is the key factor affecting the load capacity and service life of transformers. For the early detection of transformer winding hotspot temperature anomalies, a new prediction model for the hotspot temperature fluctuation range based on fuzzy information granulation (FIG) and the chaotic particle swarm optimized wavelet neural network (CPSO-WNN) is proposed in this paper. The raw data are firstly processed by FIG to extract useful information from each time window. The extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On this basis, the error backpropagation process can be realized as written in Equation (10) Collectively, it can be observed that the initial positions of particles and the velocity update algorithm are of great significance to the convergence of the WNN model. Given the good randomness and exploratory characteristics of the chaos method [29], chaos chaotic properties are applied in the PSO to enhance the optimization effects of the WNN model.…”
Section: Parameter Optimization Methods For Wnn Based On Cpsomentioning
confidence: 99%
“…On this basis, the error backpropagation process can be realized as written in Equation (10) Collectively, it can be observed that the initial positions of particles and the velocity update algorithm are of great significance to the convergence of the WNN model. Given the good randomness and exploratory characteristics of the chaos method [29], chaos chaotic properties are applied in the PSO to enhance the optimization effects of the WNN model.…”
Section: Parameter Optimization Methods For Wnn Based On Cpsomentioning
confidence: 99%
“…Combining Equations (2)-(5), the following relationship in terms of the reluctance and flux density can be drawn: (6) where B i is the flux density of the i-th magnetic segment.…”
Section: Steinmetz Equation (Mse) General Steinmetz Equation (Gse)mentioning
confidence: 99%
“…The parts with strong vibration signal are more likely to have fault accidents occur [27]. High signal-to-noise ratio can also be obtained by selecting a strong vibration area of the transformer winding [28]. According to the model studied in this paper, the vibration signal near the winding is strong.…”
Section: Transformer Short-circuit Experimentsmentioning
confidence: 99%